2017
DOI: 10.1016/j.scriptamat.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer-thick TiO precipitation in V-4Cr-4Ti alloy induced by proton irradiation

Abstract: We have characterised to atomic resolution the mono-layer thick TiO-type precipitate induced by proton irradiation in V-4Cr-4Ti alloy at the coarsening radiation-induced interstitial a/2⟨111⟩ dislocation loops expected to exert a minimal effect on the precipitate formation. This monolayer-thick precipitate constitutes an early stage in the radiationinduced aging process of V-4Cr-4Ti at low temperatures, and can potentially absorb additional light elements in reactor environments. 1Moor Row, November 24, 2016 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Small precipitates formed near the grain boundary or large bulk precipitates and the precipitate was Ti(CON) titanium-oxycarbonitride precipitate on a habit pane of {100}. The nature of the Ti(CON) precipitate has been reported by Impagnatiello [21][22][23]. In the thermal creep test, it is likely that Ti(CON) precipitates are formed along with defect sinks such as grain boundaries and bulk precipitates where the thermal vacancy is absorbed preferentially.…”
Section: Discussionmentioning
confidence: 89%
“…Small precipitates formed near the grain boundary or large bulk precipitates and the precipitate was Ti(CON) titanium-oxycarbonitride precipitate on a habit pane of {100}. The nature of the Ti(CON) precipitate has been reported by Impagnatiello [21][22][23]. In the thermal creep test, it is likely that Ti(CON) precipitates are formed along with defect sinks such as grain boundaries and bulk precipitates where the thermal vacancy is absorbed preferentially.…”
Section: Discussionmentioning
confidence: 89%
“…These results show that these impurities strongly affect the clustering of He in vacancies and the stability of the He n -vacancy type clusters. More recently, Impagnatiello et al [34][35][36] characterized the precipitate of V-4Cr-4Ti by proton irradiation at low temperature using high-resolution electron microscopy. They confirmed that the monolayer-thick TiO precipitate constitutes an early stage in the irradiation-induced aging process of V-4Cr-4Ti and the TiO-precipitate has a NaCltype structure.…”
Section: Tungsten Wwwspringercom/42864mentioning
confidence: 99%
“…Heavy ions are of particular interest in radiation damage studies as although their range in a material is limited, they create large amounts of damage in their short path. Some of these studies include candidate materials for plasma-facing walls and structural materials in fusion reactors [14][15][16][17], structural components for fuel assemblies inside nuclear cores [18,19], as well as investigation of potential new materials for use in such extreme environments [20,21].…”
Section: Accelerator Systemsmentioning
confidence: 99%